ANALYSIS OF PROJECT BASED LEARNING MODELS - Mamonto, Saifullah; Mashudi, Imam (Indonesian Journal of Social Science and Education (IJOSSE), 2025)
This analysis of the project-based learning (PBL) model aims to examine its effectiveness in improving student learning outcomes. PBL, as a constructivist approach, emphasizes learning through real experiences and authentic problem solving. This analysis includes the definition, main characteristics, theoretical basis, implementation steps, teacher roles, advantages, challenges, and strategies to overcome challenges in PBL. Assessment in PBL is also discussed, including formative, summative, rubric, and self- and peer assessment. The results of the analysis indicate that PBL has the potential to improve students' motivation, engagement, 21st century skills, and conceptual understanding. However, the implementation of PBL requires careful planning, high teacher skills, and adequate resources. With the right strategy, PBL can be an effective learning approach to prepare students for real-world challenges.